(untitled) (Homoeopathy for All, 2025)
Post-menopause is a critical phase in a woman’s life characterized by the cessation of menstruation and a wide range of physiological and psychological changes. Common symptoms include hot flashes, night sweats, mood fluctuations, sleep disturbances, and decreased bone density. While conventional hormone replacement therapy (HRT) remains a standard treatment, it carries potential risks and contraindications for some women. Homeopathy, a holistic system of medicine, offers an individualized approach that may provide symptomatic relief with minimal side effects. This article reviews the role of homeopathy in managing postmenopausal symptoms, highlights key remedies such as Lachesis, Sepia, Sulphur, and Calcarea carbonica. The potential of homeopathy as a complementary or alternative option is explored, emphasizing the importance of individualized remedy selection and patient-centred care. Further research is encouraged to validate the efficacy and safety of homeopathic interventions in postmenopausal health.